Facilitator's Guide to Participatory Decision-Making - Kaner, Sam (John Wiley & Sons, 2014)
Unleash the transformative power of face to face groups The third edit ion of this ground–breaking book continues to advance its mission to s upport groups to do their best thinking. It demonstrates that meetings can be much more than merely an occasion for solving a problem or cre ating a plan. Every well–facilitated meeting is also an opportunity to stretch and develop the perspectives of the individual members, there by building the strength and capacity of the group as a whole. This fu lly updated edition of The Facilitator's Guide to Participatory Decisi on–Making guides readers through the struggle and the satisfaction of putting participatory values into practice, helping them to fulfill th e promise of effective group decision–making. With previous editions a lready embraced by business and community leaders and consulting profe ssionals around the world, this new book is even more insightful and e asy to use. New for this edition: 60 pages of brand new skills and too ls Many new case examples Major expansion and reorganization of the ad vanced sections of the book. New chapter: Teaching A Group About Group Dynamics Doubled in size: Classic Facilitator Challenges. Substantial ly improved: Designing Realistic Agendas now three chapters, with wise , insightful answers to the most vexing questions about meeting design .